2006
DOI: 10.1007/s11099-006-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performances of five Cypripedium species after transplanting

Abstract: Photosynthesis and leaf traits of five species in genus Cypripedium were compared in natural habitats and transplant nursery to develop effective strategy for cultivation and conservation. Among five species, C. guttatum had the highest photosynthetic capacity (P Nmax ) in the natural habitat and nursery, while C. lichiangense the lowest. The differences in P Nmax among species were correlated with leaf N content (LNC) and leaf dry mass per unit area (LMA). After transplanting from natural habitats to nursery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Previous studies indicate that leaf physiological functions in the same genera of Paphiopedilum and Cypripedium showed many interspecific similarities (Donovan and Arditti 1984;Johnson 1992;Zhang et al 2006). Thus, only P. armeniacum and C. flavum were selected to investigate the physiological functions because of the limited experimental materials.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Previous studies indicate that leaf physiological functions in the same genera of Paphiopedilum and Cypripedium showed many interspecific similarities (Donovan and Arditti 1984;Johnson 1992;Zhang et al 2006). Thus, only P. armeniacum and C. flavum were selected to investigate the physiological functions because of the limited experimental materials.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In one study, a reduction of the "a/b" ratio was reported in shaded plants (ZHANG et al, 2006(ZHANG et al, , 2008 due to an increase in the production of accessory pigment "b", which is important for optimizing the efficiency of photosystem II under conditions of shade or stress (KOIKE et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The extracts were filtered, diluted to 50 mL and evaluated in a spectrophotometer at wavelengths λ= 645 and 663 nm. Chlorophyll contents "a" and "b" and the total chlorophyll were calculated based on the following equations: chlorophyll "a" (μg mL (KOIKE et al, 2001;ZHANG et al, 2006ZHANG et al, , 2008. The treatments were established by providing nitrogen substitution in the proportions presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N concentrations in orchid leaves varied around 2.00% and corresponded with a low to sufficient level reported for orchids (Jones et al, 1991;Arditti, 1992). It is well established that nitrogen concentration in leaves has positive correlation with photosynthesis capacity (Zhang et al, 2006) and some Cypripedium species have a greater photosynthesis adaptation ability than narrowly specific species (Zhang et al, 2006a).…”
Section: Plant Growth Requires Sufficient Macronutrient Level In Soilmentioning
confidence: 99%